Academic Problems Facing Diploma in Education Students in the Specialized Teaching Methods Course from Their Perspectives A Field Study on a Sample of Diploma in Education Students at the Faculty of Education, Lattakia University (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The aim of the research was to identify the academic problems facing Diploma in Education students in the Specialized Teaching Methods course from their perspectives at the Faculty of Education, Lattakia University, and to reveal differences in the academic problems facing students according to variables (gender, number of years of study, academic specialization). The descriptive analytical approach was adopted, and the sample included (86) male and female Diploma in Education students, to whom a questionnaire consisting of (17) statements was administered. The research results showed that the sample members' assessment of the academic problems they faced in the course ranged from low to medium, while the course instructor's assessment ranged from medium to high, and the educational media assessment ranged from medium to high. The research results also revealed no statistically significant differences between the sample members' responses regarding the academic problems they faced in the Specialized Teaching Methods course based on gender and years of study. However, there were statistically significant differences based on academic specialization.
Keywords: Academic problems, diploma students, Specialized Teaching Methods course.